PENGARUH FITUR PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE OPPO DENGAN WORD OF MOUTH SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Pengguna Smarphone Oppo Mahasiswa manajemen FEB Unisma 2015) - Moh. Abd Wahid Al jamil; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This research aims to find out and analyze the influence of product features on the purchasing decision of Oppo mobile phones with word of mouth as an intervening variable for students using Smartphone Oppo at FEB Malang Islamic University. The sample in this study was the FEB Management students of Malang Islamic University in the 2015 academic year who had used Oppo Smartphone, which numbered 95 people. Data collection is done by distributing questionnaires. The data analysis used in this study used validity, reliability, normality, path analysis, t test and sobel test. The results of the research show that Product Features have a direct effect on Purchasing decisions, Product Features have a direct effect on word of mouth (WOM). word of mouth (WOM) has a direct effect on purchasing decisions, product features indirectly influence purchasing decisions through WOM. Word of mouth can mediate between Product Features and Purchase decisions. Keywords: Product Features, Purchasing Decisions, Word Of Mouth.